Обработка изображений в ИРЭ НАН Украины - Корниенко, Ю.В. (Інститут радіофізики і електроніки ім. А.Я. Усикова НАН України, 2008)
Обзор исследований и разработок, выполненных в ИРЭ НАНУ в области аналоговой и цифровой обработки изображений за почти 40-летний период. Кратко излагаются научные основы обработки изображений, история возникновения этих работ в ИРЭ, основные этапы фундаментальных и прикладных исследований. Описаны созданные в ИРЭ на первых этапах работы когерентно-оптическая установка и система цифровой обработки изображений. Кратко изложена суть исследований, проводимых в ИРЭ в последнее время. Огляд досліджень та розробок, які виконано в ІРЕ НАНУ у галузі аналогової та цифрової обробки зображень за майже сорокалітній період. Коротко викладено наукові основи обробки зображень, історія виникнення цих робіт в ІРЕ, основні етапи фундаментальних та прикладних досліджень. Описано створені в ІРЕ на перших етапах роботи когерентно-оптична установка та система цифрової обробки зображень. Коротко викладено суть досліджень, які проводяться в ІРЕ в останній час. An overview is given of the research and development work that has been carried out in the field of analog and digital image processing over the last 40 years at the Usikov Institute of Radiophysics and Electronics (IRE) of the NASU. The scientific foundations of image processing, the historical milestones that bring us back to the pioneering research efforts in the image processing techniques, the main stages of these fundamental and applied investigations are briefly outlined. The initial phases of operations of a coherent-optical setup and a digital image processing system developed at the above-mentioned Institute are described. The essentials of the studies that have recently been made at the IRE are summarized.